2015
DOI: 10.1097/apo.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Topical 5% Natamycin With Oral Ketoconazole in Filamentous Fungal Keratitis

Abstract: Although safe, oral ketoconazole did not add significant benefit to topical natamycin therapy in treating deep fungal keratitis. The efficacy of newer antifungal agents and drug delivery routes needs to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…On average, it took 6 weeks to 6 months to treat a case of fungal keratitis. Our observation did not match the study by Rajaram et al 19 which found that oral antifungal therapy did not add significant benefit to topical natamycin therapy in treating deep fungal keratitis. The diagnostic validity of traditional clinical features such as dry, raised, leathery ulcers with thick and immobile hypopyon (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…On average, it took 6 weeks to 6 months to treat a case of fungal keratitis. Our observation did not match the study by Rajaram et al 19 which found that oral antifungal therapy did not add significant benefit to topical natamycin therapy in treating deep fungal keratitis. The diagnostic validity of traditional clinical features such as dry, raised, leathery ulcers with thick and immobile hypopyon (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…We had earlier published a study which revealed no added benefit in supplementing oral ketoconazole to topical antifungals in fungal keratitis. [ 25 ] Since systemic Voriconazole is being widely used for systemic aspergillosis, we decided to perform a randomized clinical trial using oral Voriconazole supplementation to arrive at a definitive conclusion. This prospective study, termed MUTT II, was performed in India and Nepal and compared oral Voriconazole with placebo in addition to topical antifungals in the treatment of severe fungal keratitis.…”
Section: Drug Trialsmentioning
confidence: 99%
“…Although single case reports show some promising results, they were never replicated in larger clinical trials. Most recent studies suggest that 5% natamycin is a drug of choice, although it is not commercially available in Poland [20,21,24,25,26]. Due to pregnancy, in the presented patient treatment was limited to topical medications; therefore, medication commenced with voriconazole, with natamycin added as soon as was possible to import it from a foreign pharmacy.…”
Section: Case Reportmentioning
confidence: 99%
“…Both agents have limited ability to penetrate the corneal epithelium; therefore, some authors suggest repeatable epithelial debridement before eyedrop application [13]. Synergistic effect has been pursued in several studies, combining both topical natamycin with voriconazole [14,20], topical natamycin with systemic ketoconazole [21], topical and systemic voriconazole [22], voriconazole with micafungin [23]. Although single case reports show some promising results, they were never replicated in larger clinical trials.…”
Section: Case Reportmentioning
confidence: 99%